Karp's cell and molecular biology - Iwasa, Janet; Marshall, Wallace F., 1968-; Karp, Gerald (2020)
"In the 9th edition we have introduced two new sections for each chapter. Green Cells sections highlight important features of plant cell biology that underscore central concepts from each chapter and illustrate how the study of plants has informed our understanding of cells in general. Engineering Linkages sections address the interface between cell biology and biomedical engineering, and are intended to make the cell biology material more accessible for engineering students while introducing biology students to important trends in bioengineering."--
Includes index.
Revised edition of: Karp's cell and molecular biology : concepts and experiments / Gerald Karp, Janet Iwasa, Wallace Marshall. 8th edition. 2015.
Keywords: Cytology; Molecular biology